Glutaraldehyde-enhanced autofluorescence as a general tool for 3D morphological imaging - Niemeläinen, Miika; Haapanen-Saaristo, Anna-Mari; Koskinen, Leena M.; Gullmets, Josef; Peuhu, Emilia; Meinander, Annika; Calhim, Sara; Paatero, Ilkka (The Company of Biologists, 2025)
Routine histochemical techniques are capable of producing vast amount of information from diverse samples types, but these techniques are limited in their ability to generate 3D information. Autofluorescence imaging can be used to analyse samples in 3D but it suffers from weak/low signal intensities. Here, we describe a simple chemical treatment with glutaraldehyde to enhance autofluorescence for 3D fluorescence imaging and to generate detailed morphological images on whole-mount samples. This methodology is straightforward and cost-effective to implement, suitable for a wide range of organisms and sample types. Furthermore, it can be readily integrated with standard confocal and fluorescence microscopes for analysis. This approach has the potential to facilitate the analysis of biological 3D structures and research in developmental biology, including studies on model and non-model organisms.